Pyramid no. 2 )

Lateral area = 1/2* perimeter * slant height

faces = 6 and edge= 8 cm. so total perimeter of base = 8*6 = 48 cm

slant height = 12 cm

lateral area= 1/2*48*12 cm square = 288 cm square

Surface area = Lateral area + area of base

So, area of base = 3 (root 3)/2 * a = 3 (root 3)/2 * 8 = 166.28 cm

So, surface area = 166.28 + 288 cm square = 454.28 cm square

pyramid no. 3 ) discussing with u next

pyramid no. 3 )

slant height^2 = height ^2+ (base/2)^2 (pythagoras theorem)

or slant height ^2 = 15^2+8^2 = 225+ 64 = 289

or slant height = 17 cm

so base perimeter = 16*4 = 64 cm

so lateral area = 1/2* perimeter * slant height = 1/2* 64* 17 = 32*17 cm square = 544 cm square

area of base = 16*16 = 256 cm square

so surface area = lateral area + area of base

= 256+544 = 800 cm square

pyramid no. 4 )

total perimeter of base = 15*3 = 45 inches

slant height = 20 inches

lateral area= 1/2*45*20 inches square = 450 cm square

So, area of base = 15*15 = 225 inches square

So, surface area = 450+225 inches square = 675 inches square

Hope it helps :) and release the payment with a 5 star review and ratings!

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up